Efektivitas Investasi dan Pembiayaan Internal: Fenomena Manajer Terlalu Percaya Diri di Pasar Modal Indonesia - Ramdani, Deni; Herawati, Heni (Postgraduate Program Merdeka University, 2020)
Overconfident managers create biases that make them overvalue their company and its investments. This study takes a sample of companies that are listed in the Indonesia Stock Exchange, for the years 2013-2017. Companies that are listed on the LQ 45 index have high liquidity so that the stock is active so it doesn't interfere with the accuracy of the research being carried out. The results showed that internal funding has a significant posi-tive relationship with company investment. This shows that the more internal financing, the greater the scale of the investment the company will make. Internal financing and overinvestment have a significant positive correlation. So that companies tend to over-invest. Internal finance has a dual role to play in investment. One side of the bias to im-prove investment efficiency by increasing the scale of investment and reducing the scale of investment, on the other hand it can cause excessive investment.DOI: https://doi.org/10.26905/afr.v3i2.3834